Remote ancestors or scientific evidence? Pre-Hispanic mummies from the Canary Islands in the media - Maria Meneses Fernández; Maria García Morales; Fernando Estévez González (Journal of Biological Research, 2005)
People have always been fascinated by mummies. In Tenerife (Canary Islands, Spain), the mummified remains of its ancient inhabitants are a source for superstition, fear, respectful recognition, collecting greediness, nationalistic pride, or scientific interest in modern Canarians. This paper discusses the different values and meanings that the cultural industry-mass media included-has bestowed on these mummies. Sensationalist approaches, identity issues, and diversions from the scientific discourse inserted in the news, reports, and opinion articles published in local newspapers and Spanish periodicals are examinedparticularly the influence exerted by the Archaeological Museum by way of scientific publications and press releases regarding the mummies’ social and political uses. This paper also analyses how the museum’s visitors perceive the displayed mummies and their accompanying messages, in order to track if previous ideas released in the media have influenced them.